EXTH-84. A NOVEL DUAL-SPECIFIC CHIMERIC ANTIGEN RECEPTOR T CELL WITH HIGH SPECIFICITY FOR EGFR AND EGFRVIII IMPROVES SURVIVAL IN EGFR EXPRESSING MEDULLOBLASTOMA. (14th November 2022) - Wilson, Joseph; Wilkinson, Daniel; Ryan, Katherine; Bigner, Darell; Chambramohan, Vidya; Fecci, Peter
Abstract: BACKGROUND: Medulloblastoma is the most common malignant brain tumor in children 0-19 years of age and current treatment requires surgical resection, followed by high dose chemotherapy and radiotherapy. Therapy carries high morbidity, with late effects including neurocognitive decline, endocrine dysfunction, and subsequent malignancies. Chimeric antigen receptor (CAR) T cell therapy presents the potential for less toxic and more effective treatment for medulloblastoma. Epidermal growth factor (EGFR) is expressed in medulloblastoma derived cell lines and appears to serve an important role in the metastatic potential of this tumor type. D2C7 is a recombinant monoclonal antibody short chain variable fragment (scFv) with dual specificity, binding to wild type EGFR (EGFRwt) and its mutant EGFR variant III (EGFRvIII). We previously developed a novel, third-generation chimeric antigen receptor T-cell construct utilizing the D2C7 scFv and performed analysis on both glioblastoma and medulloblastoma tumor models. METHODS: U87 and U87vIII glioblastoma and DAOY medulloblastoma cell lines were characterized by flow cytometry to evaluate for EGFRwt and EGFRvIII expression. Cytotoxicity assays were performed utilizing flow cytometry on serially diluted effector: target ratios of U87, U87vII, and DAOY mixed with D2C7 CAR. DAOY was orthotopically implanted into the frontal lobe of NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice. After tumor implantation, D2C7 CAR was introduced within the tumor bed. RESULTS: EGFR was detected in U87, U87vIII, and DAOY on flow analysis. EGFRvIII was expressed only on U87vIII. D2C7 CAR demonstrated effective in vitro cytotoxicity against all three cell lines with >90% cytotoxicity achieved at an effector: target ratio of 2.5:1. In vivo, D2C7 CAR treatment significantly prolonged survival compared to treatment with mock CAR. CONCLUSION: D2C7 CAR demonstrates efficacy in vitro and in mouse models of medulloblastoma and glioblastoma. Future steps in our work will set out to assess the D2C7 CAR in NSG mice with DAOY in the posterior fossa.